PENGARUH FAKTOR INTERNAL ORGANISASIONAL DAN KARAKTERISTIK PEGAWAI TERHADAP IMPLEMENTASI SISTEM PENGUKURAN KINERJA INSTANSI PEMERINTAH (SAKIP) DI PEMERINTAH PROVINSI BANTEN - Perkasa, Guruh Juni (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This research examines the effect of the internal factors of organizational and individual characteristics to the implementation of Government Performance Accountability System (SAKIP) in Banten Provincial Government. The object of this research is the whole Apparatus of Civil State (ASN) in Banten Provincial Government with samples Kassubag Program, Evaluation and Reporting and the Secretary of the respective regional organization (WTO) as much as 78 respondents. Data was analyzed by using SEM (Structural Equation Model) through SmartPLS program (Partial Least Square) version 3.0.The results of this study expressed the commitment of management, training of the organization's response to changes in the draft (which is the internal factors of the organization) and self efficacy and conscientiousness (which is an individual character) has a positive effect on the implementation SAKIP in Banten Provincial Government.Keywords : Internal Factor of Organizational, Individual Characteristics, Institutional Isomorphism, SAKIP